METHODS AND TOOLS OF IMPLEMENTING PROBLEM TEACHING TECHNOLOGY IN STUDYING THE SCIENCE OF "MILITARY PEDAGOGY AND PSYCHOLOGY" (American Journal of Interdisciplinary Research and Development, 2023)
This article examines the methods and tools used in the implementation of problem-based educational technology, including in the field of "Military pedagogy and psychology". The purpose of the article is to reveal the methods and means of implementing problem-based educational technology in the study of " pedagogy and psychology". Based on the analysis of relevant literature, concepts such as "Problematic educational technology", "Problematic educational methods", "Problematic educational tools" are presented. Methods of problem-based educational technology implementation, such as case method, monologue presentation method, heuristic presentation method, project-based teaching method, etc., are presented.